2021
DOI: 10.3390/app112110060
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Free-Synthesized ZnSe/ZnS Core/Shell Quantum Dots for White Light-Emitting Diodes

Abstract: Blue-light-emitting ZnSe core (C) and ZnSe/ZnS core/shell (C/S) quantum dots (QDs) were synthesized with phosphine-free precursors by a thermal decomposition method in paraffin oil solvent and applied to QD-converted light-emitting diodes (LEDs). The optical properties of the synthesized ZnSe C and ZnSe/ZnS C/S QDs were characterized by absorption spectroscopy and photoluminescence spectroscopy. Additionally, the quantum efficiency of the QDs was investigated. Their structural properties were studied with X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Core/shell CIS/ZnS QDs exhibiting up to 97% FLQY have been reported . They are attractive for various applications such as white light-emitting diodes (LEDs), solar cells, and bioimaging due to their low toxicity and excellent visible FL properties. …”
Section: Introductionmentioning
confidence: 99%
“…Core/shell CIS/ZnS QDs exhibiting up to 97% FLQY have been reported . They are attractive for various applications such as white light-emitting diodes (LEDs), solar cells, and bioimaging due to their low toxicity and excellent visible FL properties. …”
Section: Introductionmentioning
confidence: 99%
“…However, Cd is toxic, which limits the practical applications these QDs and raises concerns about their potential threats to the environment and human health 3 , 5 . Therefore, there is increasing demand for the development of Cd-free QDs 6 . ZnSe, an important II–VI semiconductor material with a wide bandgap of 2.7 eV and low toxicity, shows promise as a replacement for Cd-based QDs 7 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, monodispersed ZnSe nanocrystals have been successfully prepared by various solution-based methods, including hot-injection and heating methods 12 . In the hot-injection method, a reagent is injected into a hot reaction solution at room temperature, causing burst homogeneous nucleation, followed by slow growth of the QDs 6 . Moreover, other studies have been reported that Zn/Se ratios that differ from 1:1 do not result in improved optical properties of ZnSe QDs 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%